Analisis Perkembangan Tokoh Yoonjae Dalam Novel Almond Karya Shon Won-Pyung - Yohanna Valentina Damanik; Evi Nicky Triwahyuni; Eva Dwi Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to look at the cognitive development experienced by the character Yoonjae in the Novel Almond. The work taken is entitled Almond by Shon Won-Pyung. The problem of this research is how the cognitive development of the character Yoonjae in the novel is. The method used is qualitative descriptive research using Piaget's theory of cognitive development. The results obtained indicate an increase in cognitive development in the form of development in the operational stage, concrete operational stage and formal operational stage in the character Yoonjae in the novel.